2012
DOI: 10.3109/03008207.2012.679368
|View full text |Cite
|
Sign up to set email alerts
|

Elastin-Derived Peptides Induce Inflammatory Responses through the Activation of NF-κB in Human Ligamentum Flavum Cells

Abstract: The formation of fibrotic tissue in the ligamentum flavum (LF) is usually preceded by breakdown of elastic fibers. Elastin-derived peptides (EDPs) from breakdown of elastic fibers display a wide range of biological activities in a variety of cells, but there is minimal information regarding the involvement in the processes of LF hypertrophy. The aim of this study is to elucidate the effects of EDPs on cultured human LF cells and to investigate their molecular and biochemical mechanisms. Human LF cells were obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The ECM can also drive cancer cell gene expression, signal transduction, cell morphology, cell survival, and motility [ 124 ]. Changes in ECM can also cause CAFs to secret pro-inflammatory markers, thereby enhancing cancer progression [ 125 , 126 ]. In physical terms, it appears that the ECM can regulate cancer cell invasion via multiple parameters, including density, orientation, stiffness, and organisation of the matrix fibres.…”
Section: Possible Mechanisms For the Involvement Of Stromal Ar Sigmentioning
confidence: 99%
“…The ECM can also drive cancer cell gene expression, signal transduction, cell morphology, cell survival, and motility [ 124 ]. Changes in ECM can also cause CAFs to secret pro-inflammatory markers, thereby enhancing cancer progression [ 125 , 126 ]. In physical terms, it appears that the ECM can regulate cancer cell invasion via multiple parameters, including density, orientation, stiffness, and organisation of the matrix fibres.…”
Section: Possible Mechanisms For the Involvement Of Stromal Ar Sigmentioning
confidence: 99%
“…TGM2 also can be induced directly by NF-κB activation to modulate inflammatory response (12). Furthermore, elastin-derived peptides from breakdown of elastic fibers could also induce inflammatory responses through the activation of NF-κB cascades (43). This study further demonstrates that centrifugal force induces TGM2 gene expression and enzyme activity in human ligamentum flavum cells.…”
Section: Discussionmentioning
confidence: 56%
“…NF-κB is highly activated at sites of inflammation in diverse diseases and can induce transcription of proinflammatory cytokines, chemokines, adhesion molecules, and inducible enzymes, mainly mediating cellular responses to damage, stress, and inflammation [ 29 ]. It has been reported that NF-κB plays a crucial role in the production of inflammatory mediators in LF tissues induced by many cytokines or proteins [ 17 , 30 ]. Here, we also found that the NF-κB pathway was essential for leptin-induced IL-6 expression in LF cells.…”
Section: Discussionmentioning
confidence: 99%